2011
DOI: 10.1111/j.1467-8489.2010.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Research and productivity in Thai agriculture

Abstract: This paper examines the impact that publicly funded agricultural research has on productivity in crop production within Thailand. It tests empirically the two hypotheses that, first, publicly funded research and development (R&D) in crop production is a significant determinant of total factor productivity (TFP) in the crop sector and, second, that its social rate of return is high. The statistical analysis applies error correction methods to national level time series data for Thailand, covering the period 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Previous studies measured agricultural TFP and empirically analyzed several causative factors including economies of scale (Thirtle et al 2008), research and development (R&D) activities (Alene 2010), human capital (Astorga et al 2011), soil quality (Jayasuriya 2003), and public facilities such as roads, and irrigation and drainage facilities (Suphannachart and Warr 2010;Chen, et al 2008).…”
Section: Literature Review and Scientific Questionsmentioning
confidence: 99%
“…Previous studies measured agricultural TFP and empirically analyzed several causative factors including economies of scale (Thirtle et al 2008), research and development (R&D) activities (Alene 2010), human capital (Astorga et al 2011), soil quality (Jayasuriya 2003), and public facilities such as roads, and irrigation and drainage facilities (Suphannachart and Warr 2010;Chen, et al 2008).…”
Section: Literature Review and Scientific Questionsmentioning
confidence: 99%
“…The Thai government could consider investing in empowering farmers to better compete through training, agricultural credit, and infrastructure investment (Boselie et al, 2003). Government investment in agricultural research, which in the past has been a strong driver of agricultural productivity improvement, has been falling in recent years (Suphannachart & Warr, 2011). A program of empowering Thai farmers through improving their human and material resources and through improved access to technology, training, and credit for agricultural inputs would allow them to participate in and benefit more fully from trade liberalization and improve food and economic security for Thailand's poorest group (Zamroni, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the long-run elasticity of TFP with respect to climate change was 0.506, while that of R&D expenditure was 0.497. Suphannachart and Warr (2011) investigated the impact of public investment in agricultural R&D on TFP in Thai agriculture for crop production. They used error correction methods for the period of 1970-2006.…”
Section: Introductionmentioning
confidence: 99%